Citizen Science as a Tool for Augmenting Museum Collection Data from Urban Areas - Spear, Dakota M.; Pauly, Gregory B.; Kaiser, Kristine (Frontiers in Ecology and Evolution, 2017)
Museum collections are critical to contemporary biological research, but museum acquisitions have declined in recent decades, hampering researchers’ ability to use collections to assess species responses to habitat modification, urbanization, and global climate change. Citizen science may be a key method to bolster museum collections data, particularly from urban regions, where ongoing data collection is critical to our understanding of ecosystem dynamics in a highly modified and variable landscape. In this study, we compare data collected as part of the citizen science project Reptiles and Amphibians of Southern California (RASCals), hosted on the platform iNaturalist (www.inaturalist.org), to data in the VertNet database (www.vertnet.org), which houses millions of museum collection records from over 250 natural-history collections, for four focal species, including a native lizard of conservation concern that has declined with urbanization, a native lizard that is widespread in urban areas, and two invasive aquatic species. We compared numbers of VertNet records over time to modern RASCals records, and the number of records collected from urban, suburban, and protected areas from both databases. For all species, citizen science records were generated much more rapidly than museum records. For three of our four focal species, RASCals participants over 27 months documented from 70% to 750% more records than were added to the VertNet database after 1990. For the urban-tolerant southern alligator lizard, RASCals participants collected nearly 45 times more modern urban records than are contained in the VertNet database. For all other species, the majority of RASCals records were collected within suburban or other highly modified landscapes, demonstrating the value of citizen science for collecting data within urban and suburban ecosystems. As new museum acquisitions decline, citizen science projects like RASCals may become critical to the maintenance of modern species distribution data.